1985
DOI: 10.1099/00221287-131-5-1023
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of TOL Plasmid Deletion Mutants in Pseudomonas putida MT15 and Their Reversion by Tandem Gene Amplification

Abstract: ~~~Pseudomonasputida MT15 contains a large plasmid, pWW15, of about 250 kbp, which encodes the genes for toluene and xylene catabolism. Growth on benzoate selects strongly against the wild-type and results in the segregation of three phenotypically distinguishable mutant types. (1) B1 mutants, which have lost the complete plasmid.(2) B3 mutants, in which the plasmid has undergone a large deletion of about 90 kbp which appears to affect the regulation of the catabolic enzymes; these mutants retain the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1986
1986
1991
1991

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 4 publications
(10 reference statements)
1
34
1
Order By: Relevance
“…It seems reasonable to assume that benzoate can be metabolized via the plasmid-encoded pathway in strain UCC22. MT14, MT15 and MT20 produce several classes of phenotypically distinguishable TOL-deletion mutants Pickup & Williams, 1982;Keil & Williams, 1985) and it has been suggested that such TOL plasmids have regions of homology which act as 'hotspots' for recombinational deletion events (Williams et al, 1988). In the case of pWWO growth of the host on benzoate was found to highlight two effects, either complete plasmid loss or deletion of a specific 39 kbp region bearing all the catabolic genes (Bayley et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable to assume that benzoate can be metabolized via the plasmid-encoded pathway in strain UCC22. MT14, MT15 and MT20 produce several classes of phenotypically distinguishable TOL-deletion mutants Pickup & Williams, 1982;Keil & Williams, 1985) and it has been suggested that such TOL plasmids have regions of homology which act as 'hotspots' for recombinational deletion events (Williams et al, 1988). In the case of pWWO growth of the host on benzoate was found to highlight two effects, either complete plasmid loss or deletion of a specific 39 kbp region bearing all the catabolic genes (Bayley et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…functional, cells growing by the chromosomal pathway become amplified due to faster growth rate on the substrate (Nakazawa & Yokota, 1973;Williams & Murray, 1974). Such amplified cells are plasmid 'cured' or have suffered plasmid deletions (Williams & Worsey, 1976;Kunz & Chapman, 1981 ;Pickup &Williams, 1982;Pickup et al, 1983;Keil & Williams, 1985). The period of amplification varies considerably and occurs faster with TOL plasmids present in Pseudornonas MT14, MT15 and MT20 than with the archetypal TOL plasmid pWWO of Pseudornonas putida mt-2 (Paw 1) (Williams & Worsey, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Cells of Pseudomonas were grown in induced and uninduced conditions as described in Keil & Williams (1985) and cells of E. coli were grown overnight in Luria broth with addition of an appropriate antibiotic. All enzyme assays were carried out on sonic extracts of cells using previously reported methods : benzyl alcohol dehydrogenase (BADH) and benzaldehyde dehydrogenase (BZDH) (Worsey & Williams, 1975); catechol 2,3-dioxygenase (C230), 2-hydroxymuconic semialdehyde dehydrogenase (HMSD), 2-hydroxymuconic semialdehyde hydrolase (HMSH), 4-oxalocrotonate tautomerase (OT) and 4-oxalocrotonate decarboxylase (OD) (Sala-Trepat & Evans, 197 1); 2-oxopent-4-enoate hydratase (OEH) (Collinsworth et al, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…pWW 15 is one of three large, structurally related TOL plasmids, p W W 14, p W W 1 5 and pWW20, which have the characteristic property of being strongly counterselected during growth of their natural hosts in benzoate minimal media (Williams & Worsey, 1976). After about 20 generations no strains with the typical TOL phenotype can be detected in the population, which consists either of plasmid-free cells or of cells which have an altered, defective catabolic phenotype (Williams & Worsey, 1976;Pickup & Williams, 1982;Pickup et al, 1983;Keil & Williams, 1985) and which have suffered large deletions of plasmid DNA. In this paper we report the existence of two upper pathway operons and two meta pathway operons on pWW 15.…”
Section: Jx Ukmentioning
confidence: 99%
See 1 more Smart Citation